The shift toward neo‐adjuvant chemotherapy and interval debulking surgery for management of advanced ovarian and related cancers in a population‐based setting: Impact on clinical outcomes. (18th July 2017) - Nicklin, James L.; McGrath, Shaun; Tripcony, Lee; Garrett, Andrea; Land, Russell; Tang, Amy; Perrin, Lewis; Chetty, Naven; Jagasia, Nisha; Crandon, Alex J.; Nascimento, Marcelo; Walker, Graeme; et al.
Abstract : Objectives: The aim of this study was to determine the proportion of patients with advanced ovarian and related cancers (EOC+RC), treated with neoadjuvant chemotherapy and interval debulking surgery (NACT – IDS), and to determine if there was any relationship with optimal cytoreduction rates and overall survival (OS) in a state‐wide gynaecologic oncology service over time. Methods: A retrospective review was undertaken using a population‐based database of patients with stages 3 and 4 EOC+RC treated from 1982 till 2013 at the Queensland Centre for Gynaecological Cancer (QCGC). The proportion of patients treated with NACT – IDS compared with primary debulking surgery (PDS) was determined and compared with debulking rates and with the moving five‐year OS probability. Results: From 1982–2013, 2601 patients with advanced EOC+RC were managed at QCGC. No patients received NACT – IDS till 1995 when the first two patients received this treatment, rising to 55% of patients in 2013. Surgical cytoreduction rates to no macroscopic residual (R0) were achieved 32% of the time by 2006, rising to 48% in 2009, and 62% in 2013. Despite the increase in utilisation of NACT – IDS, our unit has noted a continued rise in the OS probability at five years to 45%. Conclusions: The increasing utilisation of NACT – IDS in the setting of a large centralised clinical service has been associated with increasing rates of optimal cytoreduction and survival rates have continued to rise in excess of those achieved in the trials reported to date.